Systems of production : markets, organisations and performance - Burchell, Brendan (London ; New York : Routledge, 2003)
This book presents a fresh, broad perspective on the key issues in the modern world economy, drawing in perspectives from management and business, politics and sociology economic history and law. Written in a lively and accessible style, it will present focused and comprehensive introductions to key topics, demonstrating the relevance of political economy to major debates in economics and to an understanding of the contemporary world.
Includes bibliographical references and index.
gau 27/06/14
Loans
Keywords: Industrial organization (Economic theory); Organizational effectiveness; Labor economics; Industrial relations